Preparação e caracterização de biossensores baseado na eletrocodeposição de grafeno/polipirrol/acetilcolinesterase para determinação de pesticidas em amostras de frutas e vegetais - Camargo, João Pedro Corrêa [UNESP] (2017)
A new biosensor was developed by a simple electrocodeposition of reduced graphene oxide (rGO), polypyrrole (PPy) and the enzyme acetylcholinesterase (AChE) on surface of platinum (Pt) electrode. In potential range of -0.2 to +0.5 V vs. Ag/AgCl/KCl (3.0 mol L-1), using differential pulse voltammetry (DPV), it was observed a process in + 0.1 V and this corresponds to the dimerization of electrochemical oxidation products of thiocholine, resulting in ditio-bis-choline. The biosensor developed was evaluated using DPV in the analysis of carbaryl, which inhibits the AChE enzyme action. The best results achieved were with the followings optimized conditions: 75 mV pulse amplitude, step potential of 4 mV, and a phosphate buffer solution (PBS) 0.2 mol L-1 and pH 6.0. Using these parameters was observed a linear response to carbaryl in a range of 0.1 to 0.5 µmol L-1, with a detection limit of 11.6 nmol L-1 (2.3 µg/kg), which is an appropriate limit for determination of carbaryl in the cultures which these pesticide is applied, considering the maximum reside limit allowed by Brazilian legislation. The biosensor proposed, Pt/rGO/PPy/AChE, was applied successfully in the determination of carbaryl in samples of cabbage and tomato.